This is US: Geography of evidence in top health economics journals - Hirvonen, Kalle (John Wiley & Sons, 2020)
The Journal of Health Economics and Health Economics are arguably the top two journals in the field of health economics. Together, they published 1,679 empirical research articles in the past decade (2010–2019). In line with analyses based on earlier periods, the empirical evidence in top health economics journals continues to be dominated by the United States (37% of all empirical articles), whereas studies based on low‐income countries remain rare (2%). Countries with higher disease burdens receive generally less attention from health economists publishing at the top of their field. Reflecting this, more research was published based on data from the Nordic countries (27 million people) than from sub‐Saharan Africa and South Asia regions combined (2.9 billion people). Finally, one‐third of the empirical articles did not indicate the country of evidence in the title or the abstract, possibly to signal external validity of the findings. This practice was particularly common for articles based on data from North America with more than half of the articles omitting the country of evidence from the title and the abstract. The study concludes by exploring some hypotheses that may explain these findings.